Pemilihan Layanan Subscription Video on Demand (SVOD) Menggunakan Weighted Product (WP) - Chetrina Dhea Puspita; Lacsita Devi Oktaviana; Ramadhani Galuh Candra Purtiwi; Nur Aini Rakhmawati (Program Studi Sistem Informasi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
In Indonesia, in the last few years there have been TV and movie entertainment services that can be accessed via mobile devices, PCs, and smart TVs. This service is known as Subscription Video on Demand (SVOD). SVOD services in Indonesia are very diverse. The problem that occurs is that there are many SVODs that have advantages and disadvantages. So, this makes it difficult for users to determine which SVOD services are in high demand. This research aims to determine the desired SVOD service according to predetermined criteria. In this research, the Weighted Product (WP) method is used to objectively determine which SVOD services are in high demand. 7 criteria were used which were selected based on observations and interviews with VOD service users. This research shows that Disney+ Hotstar is the chosen alternative with a final score of 0,2127. From this research, it is known that the determining criteria in the decision-making process are rating (C1), the increasing number of users (C2), and data collection (C7). This result is influenced by the new users of Disney+ Hotstar service, which increased very high compared to other SVOD services.